Although Surgical Techniques Differ, Similar Outcomes Can Be Obtained When Operating After Single Versus Multiple Anterior Shoulder Dislocations - Christopher D. Bernard, B.S; Devin P. Leland, B.S; Lucas K. Keyt, B.S; Matthew D. LaPrade, B.S; Aaron J. Krych, M.D; Diane L. Dahm, M.D; Jonathan D. Barlow, M.D; Christopher L. Camp, M.D (Elsevier, 2021)
Purpose: To compare the differences in preoperative pathology, surgical technique, and overall outcomes between patients treated surgically after a single anterior glenohumeral joint dislocation and those undergoing surgery after multiple dislocations. Methods: An epidemiologic database was used to identify all patients younger than 40 years undergoing surgery for anterior shoulder instability between January 1, 1994, and July 31, 2016, in a defined geographic area. Patient medical records were reviewed to obtain demographic information, patient history, physical examination findings, imaging findings, clinical progression, surgical details, and outcomes. Comparative analysis was performed between patients who underwent surgery after a single dislocation and those who underwent surgery after multiple preoperative dislocations. Results: The study population consisted of 187 patients who had a single anterior shoulder dislocation (n = 55) or multiple anterior shoulder dislocations (n = 132) prior to surgery. The mean follow-up period was 103.3 months (range, 0.3-328.4 months). Demographic characteristics were not significantly different between groups. Although the presence of Hill-Sachs lesions on radiographs was more common in the multiple-dislocation group (42.1%) than in the single-dislocation group (18.8%, P = .005), there were no other significant differences in concomitant pathology between groups. Latarjet procedures were more commonly performed in the multiple-dislocation group (12.5% vs 2.1% in the single-dislocation group, P = .04). There were no other significant differences in surgical techniques and characteristics between groups. Rates of survival free from recurrent instability (P = .790), revision surgery (P = .726), and progression to symptomatic osteoarthritis (P = .588) were not significantly different between groups. Conclusions: Although patients with multiple dislocations prior to surgery were more likely to show radiographic evidence of Hill-Sachs lesions and undergo the Latarjet procedure than those who received surgery after a single dislocation, no significant differences in outcomes with respect to recurrent instability, revision surgery, or progression to symptomatic osteoarthritis were found between these 2 groups at long-term follow-up. Level of Evidence: Level III, retrospective comparative study.